Antioxidant properties of Colorado grown potatoes - Al-Obeidani, Juma S., author; Stushnoff, Cecil, advisor; Holm, David, committee member; Newman, Steve, committee member; Harris, Mary, committee member (Colorado State University. Libraries, 2005)
Antioxidants are a group of compounds that provide protection against the harmful effects of free radicals and other reactive oxidants when included in the human diet. Free radicals are chemical compounds that have one or more unpaired electrons and can react with a range of biological molecules such as nucleic acid and protein, resulting in cell damage. Many environmental factors may affect free radical production. There is strong evidence that consuming more fruits and vegetables offers protection against degenerative diseases of aging such as cancer and heart disease. It is generally assumed that antioxidants in fruits and vegetables account for these beneficial effects. Potato (Solarium tuberosum L) a member of the Solanaceae family is a cool season crop and a major world food crop. Potatoes were chosen as a model for this research because preliminary results at Colorado State University demonstrated that potatoes accumulate a variety of secondary plant metabolites including vitamin C (ascorbic acid (AA)) and phenolic compounds which strongly contribute to antioxidant activity. Based on this, the objectives of these studies were to characterize the antioxidant content and radical scavenging capacity for advanced potato selections and various cultivars grown in Colorado, to determine the impact of production environment on antioxidant status, and to evaluate antioxidant heat stability for different potato cooking methods. This was accomplished by examining AA in potatoes using a high-performance liquid chromatographic (HPLC) method. Total phenolic compounds (TP) were measured using Folin-Ciocalteu reagent, and total antioxidant activity was estimated by the Trolox equivalent antioxidant capacity (TEAC) assay. AA was examined in four Colorado potato genotypes (Russet Burbank, Chipeta, CO 94183-1R/R (red flesh), and CO 94165-3P/P (purple flesh) grown in the Arkansas Valley (AV), the San Luis Valley (SLV), and at Powder Horn (PH) regions of Colorado. The colored flesh genotypes expressed higher AA than others and the warmer lower elevation site (AV) had more AA content than the cooler higher elevation site (PH). These findings provide evidence of the importance of evaluating antioxidant status of potato clones in different sites. Among cultivars examined for TP and antioxidant activity (TEAC), the colored flesh genotypes (CO 94183-1R/R and CO 94165-3P/P) had higher TP content than the russet skin (Russet Burbank) and the white flesh genotype (Chipeta). In addition, skin periderm had higher TP content than flesh or skin+flesh. Locations and cultivars examined were different in the TP and TEAC. A linear positive relationship existed between TP and TEAC in the examined genotypes (r =0.9663) indicating that TP content and ABTS radical scavenging capacity were strongly related. Potato tubers occupy a remarkable position in human diets due to the content of vitamins, minerals, and other bioactive compounds. However, the nutritional value and the quality of processed potatoes decrease significantly due to cooking methods. Sixteen Colorado grown potato cultivars were examined for their antioxidant heat stability during cooking using three different cooking methods (microwave, boil, and bake). AA, TP, and TEAC content decreased significantly after cooking in all cooking methods, with baking being the most destructive method. Knowledge and findings from this research will assist potato breeders in introducing high quality, well adapted, and more nutritive cultivars. While potatoes provide a major source of antioxidants (AA, phenolic compounds ...etc), their role in human health through dietary interventions and providing consumers with nutritionally high value products, will receive increasing attention. Finally the data presented in this research will assist potato marketing and consumer confidence.
Keywords: botany; agricultural engineering; plant pathology; food science